2016
DOI: 10.1115/1.4033215
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Bulk Modulus, Entrained Air, and Dynamic Pressure Measurements in Liquids

Abstract: Accurate static and dynamic pressure measurements in liquids, such as fuel, oil, and hydraulic fluid, are critical to the control and health monitoring of turbomachinery and aerospace systems. This work presents a theoretical and experimental study of the frequency response of pressure transducers and pressure measurement systems in liquid media. First, we theoretically predict the frequency response of pressure transducers based upon a lumped-parameter model. We then present a liquid-based dynamic pressure ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Although it occurs only after the pressure pulse is over, there are lingering effects of turbulence and persistent gas bubbles, particularly in sebacate. One could imagine that the shape of a subsequent pressure pulse might be affected by this mixed state of the fluid if the waiting time is too short [26]. We have found that one needs to wait Fig.…”
Section: Piston Movement and The "Squid" Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it occurs only after the pressure pulse is over, there are lingering effects of turbulence and persistent gas bubbles, particularly in sebacate. One could imagine that the shape of a subsequent pressure pulse might be affected by this mixed state of the fluid if the waiting time is too short [26]. We have found that one needs to wait Fig.…”
Section: Piston Movement and The "Squid" Effectmentioning
confidence: 99%
“…A look through the optical windows can serve as a partial quality control. For best results, de-gassed fluids should be used [26].…”
Section: The Main Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…The necessity for the dynamic measurement of pressure arises at low [65] and high [66] temperatures of gases and liquids [67].…”
Section: Identification Of the Dynamic Characteristics Of A Measuringmentioning
confidence: 99%
“…In recent years, several theoretical models have been proposed to simulate the dependency of the E-Modulus upon pressure and entrained air content [22,23,24,25,26]. In [27,28], based on the experimental verification of these models, have been shown that the IFAS model in [24] can simulate the behavior of the E-Modulus with higher accuracy. However, as shown in these papers, the minimum time for maximizing the input pressure are 2.5[s], which in our study is almost the steady state case.…”
Section: Introductionmentioning
confidence: 99%